1970
DOI: 10.1161/01.cir.42.3.445
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Output Response to Exercise in Patients with Inferior Vena Caval Ligation

Abstract: Studies were carried out to determine whether hemodynamic alterations may follow inferior vena caval (IVC) ligation. Five patients, aged 29 to 49 years, who had been operated upon 2 to 5 years previously, and five normal controls, aged 39 to 44 years, were studied at rest and during graded submaximal treadmill exercise. There were no significant differences in heart rate, right atrial pressure, brachial arterial pressure, oxygen consumption, or cardiac output between the patients and normals in the supine rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1974
1974
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In smaller case series, symptomatic patients with IVC ligation were characterized by limited increase in cardiac output during peak exercise by right heart catheterization [4], and limited peak oxygen uptake during cardiopulmonary exercise testing [7,8]. Measurements at anaerobic threshold may better reflect changes in cardiac hemodynamics in patients with initially low exercise capacity who may experience an improvement in PTS severity following endovascular intervention for two reasons: (1) many PTS patients do not fulfill the criteria of sufficient subject effort during cardiopulmonary exercise testing as confirmed by our study, (2) recanalization of the IVC is associated with improvement in PTS severity and venous claudication [10,15,16], and therefore may potentially improve peak exercise performance and VO 2 independent from cardiac effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In smaller case series, symptomatic patients with IVC ligation were characterized by limited increase in cardiac output during peak exercise by right heart catheterization [4], and limited peak oxygen uptake during cardiopulmonary exercise testing [7,8]. Measurements at anaerobic threshold may better reflect changes in cardiac hemodynamics in patients with initially low exercise capacity who may experience an improvement in PTS severity following endovascular intervention for two reasons: (1) many PTS patients do not fulfill the criteria of sufficient subject effort during cardiopulmonary exercise testing as confirmed by our study, (2) recanalization of the IVC is associated with improvement in PTS severity and venous claudication [10,15,16], and therefore may potentially improve peak exercise performance and VO 2 independent from cardiac effects.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with IVC occlusion, limitations in exercise performance are often attributed to venous claudication or muscular deconditioning and not necessarily to impaired cardiac preload. First reports of patients with dyspnea on exertion, have been described in the context of IVC ligation [4][5][6]. In smaller case series, symptomatic patients with IVC ligation were characterized by limited increase in cardiac output during exercise assessed by right heart catheterization [4], and limited peak oxygen uptake during cardiopulmonary exercise testing [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…44 Patients who have undergone an IVC ligation experience a 45% reduction in CO in response to exercise compared to normal controls. 45 One recent publication reported the case of a patient who developed shock secondary to acute IVC occlusion. 46…”
Section: Cardiac Outputmentioning
confidence: 99%
“…Exercise intolerance attributed to reduction in venous return from the lower limbs was first described by Varat et al in 1970 [ 37 ], who reported results from exercise right heart catheterisation in 5 patients who had previously undergone ligation of the inferior vena cava, and developed exertional dyspnoea post-operatively. None of the patients had any evidence of pulmonary hypertension.…”
Section: Causes Of Iliocaval Venous Obstructionmentioning
confidence: 99%